2019
DOI: 10.1186/s12917-019-1795-y
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus pseudintermedius septicemia in puppies after elective cesarean section: confirmed transmission via dam’s milk

Abstract: BackgroundIn humans, transmission of bacteria causing fatal sepsis in the neonates through mother’s milk has been reported. In dogs, it is believed that bacteria from canine milk are not the primary cause of neonatal infections. Staphylococcus pseudintermedius is colonizing the skin and mucocutaneous junctions in adult dogs and can act as an opportunistic pathogen. This bacterium was previously isolated from the canine milk and, although, its transmission from the dam’s milk to the newborn puppies causing a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…As pathogens responsible for septicaemia in pups are seldom responsible for mammary gland infections (Root Kustritz, 2010), early weaning is not advised since it promotes galactostasis (Davidson, 2017). However, some reports show that puppies can be affected due to the ingesta of infected milk (Schäfer‐Somi et al., 2003; Vasiu, Pop, Chirilă, et al., 2017; Zakošek Pipan et al., 2019). Keeping in mind the age of the neonates, puppies should only be removed and hand raised, with milk replacers, if the mammary glands and health status of the bitch are deteriorating, if the bitches are nervous or present pain, or if other side effects, from antibiotic‐treated milk, like transient diarrhoea in pups, are present (Barsanti, 2012; Bassu, 2017; Biddle & Macintire, 2000; Kirk, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…As pathogens responsible for septicaemia in pups are seldom responsible for mammary gland infections (Root Kustritz, 2010), early weaning is not advised since it promotes galactostasis (Davidson, 2017). However, some reports show that puppies can be affected due to the ingesta of infected milk (Schäfer‐Somi et al., 2003; Vasiu, Pop, Chirilă, et al., 2017; Zakošek Pipan et al., 2019). Keeping in mind the age of the neonates, puppies should only be removed and hand raised, with milk replacers, if the mammary glands and health status of the bitch are deteriorating, if the bitches are nervous or present pain, or if other side effects, from antibiotic‐treated milk, like transient diarrhoea in pups, are present (Barsanti, 2012; Bassu, 2017; Biddle & Macintire, 2000; Kirk, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…While, in many cases, such transmission results in the healthy colonisation of commensal S. pseudintermedius , in the puppies, it has been shown that the transmission of S. pseudintermedius , specifically MRSP, has been associated with premature death within the first 2–3 weeks of life, also known as neonatal mortality [ 66 , 79 , 80 , 81 ]. Multiple studies have reported outbreaks of neonatal mortality due to septicaemia, with S. pseudintermedius or MRSP isolated from the blood or organs of all deceased puppies [ 66 , 79 , 82 ]. Interestingly, it was found that S. pseudintermedius strains collected from the organs of puppies were found to be linked to isolates from the mother’s milk and vaginal samples, therefore indicating that the vertical transmission of pathogenic S. pseudintermedius can result in fatal sepsis in puppies [ 79 , 82 ].…”
Section: Staphylococcus Pseudintermedius : a Pamentioning
confidence: 99%
“…Multiple studies have reported outbreaks of neonatal mortality due to septicaemia, with S. pseudintermedius or MRSP isolated from the blood or organs of all deceased puppies [ 66 , 79 , 82 ]. Interestingly, it was found that S. pseudintermedius strains collected from the organs of puppies were found to be linked to isolates from the mother’s milk and vaginal samples, therefore indicating that the vertical transmission of pathogenic S. pseudintermedius can result in fatal sepsis in puppies [ 79 , 82 ]. However, the cause of neonatal mortality is multifactorial and, in addition to infections, congenital defects and low birth weight may also contribute to neonatal mortality [ 83 ].…”
Section: Staphylococcus Pseudintermedius : a Pamentioning
confidence: 99%
“…S. pseudintermedius spreads to neonates through dam's milk that has undergone cesarean section and causes neonatal septicemia resulting in mortality. Lesions are usually present on the omentum, footpad, and dermatitis called black spot disease [18].…”
Section: Canine Pyoderma Is Predominantly Caused By Staphylococcus Sppmentioning
confidence: 99%